Transparent wearable three-dimensional touch by self-generated multiscale structure - Kyun Kyu Kim (Nature Portfolio, 2019)
Touch technology holds potential for the development of smartphones and touchscreens, yet the conventional devices are usually built on separate pressure and location sensing units. Kim et al. show a flexible and transparent touch sensor capable of mapping the position and pressure at the same time.